Body composition of preschool children and relation to birth weight - Machado,Thais Costa (2014)
Objective: to evaluate the relationship between body composition of preschool children suffering from excess weight and birth weight (BW). Methods: probabilistic sample, by conglomerates, with 17 daycare centers (of a total of 59) composing a final sample of 479 children. We used Z-score of Body Mass Index (zBMI) ≥ +1 and ≥ +2, respectively, to identify preschool children with risk of overweight and excess weight (overweight or obesity). The arm muscle area (AMA) and the arm fat area (AFA) were estimated from measurements of arm circumference, triceps skin fold thickness. Results: the prevalence of risk of overweight was 22.9% (n=110) and excess weight was 9.3% (n=44). The risk of overweight and excess weight in children did not show correlation between BW and AFA, but it did with adjusted arm muscle area (AMAa) (rp= 0.21; p= 0.0107). The analysis of the group with excess weight alone also showed a positive correlation between BW and AMAa (rp= 0.42; p= 0.0047). Conclusion: among overweight children, lower BW is associated with a lower arm muscle area in early preschool age, regardless of the fat arm area presented by them.